Hubungan Antara Efikasi Diri Dengan Kesulitan Belajar Pada Siswa Kelas XII IPS SMA Negeri 1 Juwana - Elvira Usfatun Khasanah; Eka Sari Setianingsih; MA. Primaningrum (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Self-efficacy and learning difficulties are the basis of this study. The purpose of this study is to look for the relationship between self-efficacy and learning difficulties of Shiva Class XII Social Studies SMA Negeri 1 Juwana. In this study the method used is quantitative with a correlational type of research, the population in this study is as much as 150. The sample of this study was 124 students who were determined by saturated sampling techniques. The data collection technique used the Self-efficacy scale and the Learning difficulties scale.Based on the correlation test, a sig value is obtained. (2-tailed) of 0.000 < 0.05, then the hypothesis (Ha) is accepted and it can be concluded that there is a significant relationship between self-efficacy and learning difficulties in students Kels XII IPS SMA Negeri 1 Juwana. With a correlation level if viewed from the Pearson Correlation value of 0.657 which means the correlation level is moderate. Based on the F count of 92,879 with a significance level of 0.000, where the result can be interpreted as less than 0.5, it can be concluded that there is an influence between variable X (self-efficacy) and variable Y (learning difficulties) with a percentage of 43.2%.The relationship between self-efficacy and learning difficulties possessed by students is caused by the lack of self-confidence of students in subjects. The acquisition in this study can be said that if the self-efficacy of students is low, the level of difficulty experienced is higher, then vice versa if the self-efficacy of students is high, the lower the learning difficulties experienced by students.